Donativos a favor de la viuda e hijos de Manuel A. Martínez Dávila - Todd, Roberto H.; Mestre, Enrique S. (My University, 1935)
Donativos a favor de la viuda e hijos de Manuel A. Martínez Dávila.
Keywords: Martínez Dávila, Manuel A.,1883-1934